Analysis of post-crisis accounting profession readiness - Nurhasanah, Nunung; Astuti, Ernasari Widy; Rokhman, Fathur; Prawira, Andi Raditya (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The post-crisis pandemic outbreak has changed the order of life. In this new post-crisis era, various challenges arise, including in the accounting profession. This research aims to determine the skill standards needed to carry out the accounting profession in the new normal conditions. This standard is in line with data on job market demand for beginners in the accounting profession disclosed on the job vacancy site Jobstreet. The population and sample for this study were 151 job vacancies, including the categories "audit and taxation", "banking or finance"; “Finance or Investment”, and “General Accounting or Finance”. Research using descriptive methods is used to provide a detailed description of the expected qualifications and skills.The results of this research found 17 levels of community proficiency, namely: (1) having work experience; (2) have Certificates A and B; (3) know tax laws and regulations; (4) able to operate computer programs; (5) have communication skills; (6) proficient in foreign languages; (7) have an independent attitude; (8) have high initiative; (9) have a disciplined attitude; (10) teamwork/organization skills; (11) willingness to work overtime; (12) wise and thorough attitude; (13) honest attitude; (14) responsible attitude; (15) accounting skills; (16) analytical skills; (17) writing and reporting skills. It is hoped that the research results can become a reference for prospective workers to prepare themselves to enter the accounting industry. The practical implication is that prospective workers can use the results of this research as a guide to prepare themselves and improve the skills needed to face the demands of the accounting profession in the future. Thus, this research not only contributes to the development of science, but also provides valuable insights for career development amidst post-crisis changes and dynamics.